2018
DOI: 10.1002/lary.27122
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bacteria by 16S rRNA PCR and sequencing in culture‐negative chronic rhinosinusitis

Abstract: NA. Laryngoscope, 128:2223-2225, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…The fourth and fifth columns of Table 2 lists the primers used by each study for polymerase chain reaction (PCR) amplification and 16s‐rRNA gene regions for bacterial identification. Each study used swabs as the means of sampling with some variability in the site used, while Karunasagar et al 28 . and Joss et al 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fourth and fifth columns of Table 2 lists the primers used by each study for polymerase chain reaction (PCR) amplification and 16s‐rRNA gene regions for bacterial identification. Each study used swabs as the means of sampling with some variability in the site used, while Karunasagar et al 28 . and Joss et al 29 .…”
Section: Resultsmentioning
confidence: 99%
“…reported SNOT‐22 scores for their patients but did not report any further analysis related to the microbiome and the survey results. However, Karunasagar et al 28 . showed that of the 9 patients with severe SNOT‐22 scores (>70), 5 had Staphylococcus species as their most abundant, 2 had Pseudomonas , 1 had Klebsiella , and 1 Escherichia .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of vials with visible growing within the three following days allowed the calculation of the live bacteria concentration in the culture. 41 For the administration to the mice, bacterial culture was centrifuged at 4000 g during 20 min at 4°C. Then supernatant was removed, and the pellet was washed twice in anoxic PBS supplemented with antioxidants and finally resuspended in glycerol (25% vol/vol) and stored at −80°C.…”
Section: Culture Of Subdoligranulum Variabilementioning
confidence: 99%
“…Nas vias aéreas, o desbalanço do microbioma também se mostra um fator importante em doenças das vias inferiores, como em doenças obstrutivas pulmonares (60) . (61,62) . Estudos moleculares demonstraram a presença de microrganismos em seio esfenoidal, maxilar e etmoidal saudáveis (38,42) .…”
Section: Microbioma Na Rscunclassified